OP83 The challenge of finding the 'right' outcome to measure the effects of ACP – Part I. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Rietjens, J; Sudore, R; van der Heide, A; Heyland, D; Korfage, I
Abstract : Background: Advance care planning (ACP) is increasingly implemented in oncology and beyond, but a definition of ACP and recommendations concerning its use are lacking. This hinders the development of ACP programmes and the evaluation of ACP's effectiveness. Methods: We used a formal Delphi consensus process to help develop a definition of ACP and provide recommendations for its application in healthcare, policy and research. Results: Of the 109 experts (82 from Europe, 16 from North America, and 11 from Australia) who rated the ACP definitions and its 41 recommendations, agreement for each definition or recommendation was between 68–100%. ACP was defined as the ability to enable individuals to define goals and preferences for future medical treatment and care, to discuss these goals and preferences with family and health-care providers, and to record and review these preferences if appropriate. Recommendations included the adaptation of ACP based on the readiness of the individual; targeting ACP content as the individual's health condition worsens; and, using trained non-physician facilitators to support the ACP process. A list of outcome measures is also presented to enable the pooling and comparison of results of ACP studies. Conclusion: This large international Delphi panel was able to come to a consensus on an ACP definition and recommendations. This represents an important first step in providing clarity with a view to further policy and research in this field. We believe that our recommendations can provide guidance for clinical practice, ACP policy, and research.